Voluntary agreements with industries: Participation incentives with industry-wide targets - Na Li Dawson; Kathleen Segerson (Fondazione Eni Enrico Mattei (FEEM), 2000)
We develop a multiple-firm model of an industry's voluntary adoption of environmental protection measures to achieve a predetermined industry-wide emissions reduction target under an explicit threat of imposition of an emissions tax. We examine the free-riding incentive of individual firms and its impact on the viability of a voluntary approach to pollution control (VA). We find that despite the free-riding problem, there is an incentive for a sub-group of firms in an industry to participate in a VA. There always exists an equilibrium VA with at least one firm participating. A VA is strictly preferred by firms and an industry as a whole, although it is cost inefficient from society's point of view. However, if a VA can save transaction costs significantly relative to an emissions tax, it could still be socially preferred. Finally we show that the free-riding problem does not necessarily get worse with an increase in industry size. However, the cost saving to the industry and the loss to the society (excluding transaction costs) increase with the size of an industry.
Keywords: K32; D21; Q28; 330; Voluntary agreement; voluntary approach; environmental protection; free-riding; emissions tax; Umweltmanagement; Selbstverpflichtung; Trittbrettfahrerverhalten; Soziale Kosten; Theorie